2006
DOI: 10.1007/s00384-006-0174-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term manometric study of anal sphincter function after hemorrhoidectomy

Abstract: Our data support that Milligan-Morgan hemorrhoidectomy induces a complete resolution of typical manometric alterations of disease and that the excision of anal cushions is responsible only for mild and transient alteration of anal continence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
8
1
1
Order By: Relevance
“…Anal RP may decrease following haemorroidectomy. On the other hand RP is often higher than normal in patients with symptomatic haemorrhoids and recent studies have shown that although RP was decreased by surgery, it was not lower than in controls, 6 to 12 months after haemorroidectomy [38,39]. Thus, we do not believe that haemorrhoidectomy in a few patients influenced our results.…”
Section: Discussioncontrasting
confidence: 75%
“…Anal RP may decrease following haemorroidectomy. On the other hand RP is often higher than normal in patients with symptomatic haemorrhoids and recent studies have shown that although RP was decreased by surgery, it was not lower than in controls, 6 to 12 months after haemorroidectomy [38,39]. Thus, we do not believe that haemorrhoidectomy in a few patients influenced our results.…”
Section: Discussioncontrasting
confidence: 75%
“…It is known that many patients with symptomatic hemorrhoids have elevated anal resting pressure [6][7][8][9][10]. The etiology of the hemorrhoid disease is unknown and still debated; however, the elevated anal resting pressure is considered as one of the etiological factors [11].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of the hemorrhoid disease is unknown and still debated; however, the elevated anal resting pressure is considered as one of the etiological factors [11]. It has been demonstrated that the increased resting pressure is reduced in the early period after haemorrhoidectomy [9,12]. There is ongoing debate as to whether the pressure decline following haemorrhoidectomy is due to removal of the hemorrhoid anal cushions or because of prolonged retraction of the anal canal [13].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an elevation of MRP and ultra slow waves activity (USWA) in patients with haemorrhoids when compared with controls. 2 This is due to abnormal, hypertonicity of the internal anal sphincter. It is not clear if the high resting anal pressures are caused by haemorrhoids or whether they are the cause of the haemorrhoids themselves.…”
Section: Aetiologymentioning
confidence: 99%
“…Several studies have shown that the pressures in the internal anal sphincter is greatest after a patient has had haemorrhoidectomy. [2][3][4] This causes pain which leads to further increase in the pressure and so a vicious cycle ensues. There are other postulated mechanisms for experiencing post-operative pain after haemorrhoidectomy.…”
Section: Aetiologymentioning
confidence: 99%